Pemuridan sebagai Sarana Peningkatan Kualitas Rohani dalam Konteks Pertumbuhan Gereja - Samuel Elia; Samuel Herman; Joko Prihanto (Program Pascasarjana UKIM, 2024)
This article presents the role of discipleship in enhancing spiritual quality within the context of church growth. It identifies the influence of discipleship on the growth of spiritual quality among congregations and its implications for church growth. The research method employed is the qualitative literature review. The findings indicate that discipleship plays a crucial role in shaping the commitment of congregants to remain faithful to the local church, increasing their willingness to engage in ministry, and cultivating effective mission workers to support spiritual transformation. The conclusion drawn from this study is that discipleship is key to enhancing the spiritual quality of congregants, thereby supporting church growth. This paper highlights the importance of focusing on qualitative growth in fulfilling the church's mission. Moreover, it provides a better understanding of how discipleship can be an effective strategy for achieving the goals of church growth within the context of congregational spirituality.